Methods for characterizing the structure of starch in relation to its applications: a comprehensive review - Xu, Hanbin; Zhou, Jiaping; Liu, Xia; Yu, Jinglin; Copeland, Les; Wang, Shujun (Critical reviews in food science and nutrition, 2023)
Starch is a major part of the human diet and an important material for industrial utilization. The structure of starch granules is the subject of intensive research because it determines functionality, and hence suitability for specific applications. Starch granules are made up of a hierarchy of complex structural elements, from lamellae and amorphous regions to blocklets, growth rings and granules, which increase in scale from nanometers to microns. The complexity of these native structures changes with the processing of starch-rich ingredients into foods and other products. This review aims to provide a comprehensive review of analytical methods developed to characterize structure of starch granules, and their applications in analyzing the changes in starch structure as a result of processing, with particular consideration of the poorly understood short-range ordered structures in amorphous regions of granules.